Moleculer Detection of Protozoa Trichodina spp. In Gourami (Osphromenus Gourame Lac.) Larvae with The infecting 18S rRNA Gene Marking in Exs. Residence of Banyumas, Central Java - Rokhmani Rokhmani; Endang Ariyani Setyawati; Daniel Joko Wahyono (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2018)
Protozoa species of Trichodina spp. may be found in most hatchery centers in Banyumas, Purbalingga, and Banjarnegara. However, the determination of Trichodina spp. types is still based on its body’s morphological variations, not yet molecular. A research has been conducted to identify molekuler of the Trichodina spp. with the infecting 18S rRNA gene marking on the gourami larvae in Exs. Residence of Banyumas, Central Java. The research used a survey method with the samples of gourami. Amplification of 18S rRNA gene from Trichodina heterodentata was Performed using PCR technique. Primer used is Forward primer (5 ‘-AAC CTG GTT GAT CCT GCC ATG-3’) and Reverse primer (5 ‘-TGA TCC TTC TGC AGG TTC ACC TAC-3’) which produces a 600 pb amplicon of DNA. Molecular research can be a complementary identification of organisms morphologically. Amplification of the partial 18S rRNA gene may be used to identify Trichodina specifically. Gourami larvae taken from the hatchery centers in Banyumas, Purbalingga, and Banjarnegara. The results show that the detected percentage of Trichodina heterodentata genes with the infecting 18S rRNA gene marking on the gourami larvae in Central Java taken from the hatchery centers in Banyumas, Purbalingga and Banjarnegara are respectively 10%, 10%, and 45%. This research provides a benefit in mapping the presence of protozoa pathogen of Trichodina spp. in gourami hatcheries in the Former Exs. Residence of Banyumas, Central Java